Cornicle secretions by Aphis fabae (Hemiptera: Aphididae) result in age-dependent costs and improved host suitability for Lysiphlebus fabarum (Marshall) (Hymenoptera: Braconidae). Issue 5 (4th December 2017) - Parvizi, Y.; Rasekh, A.; Michaud, J.P.
Abstract: We examined the life history consequences of cornicle secretion by Aphis fabae Scopoli in second and fourth instars, and its effects on host suitability for its parasitoid, Lysiphlebus fabarum (Marshall). Cornicle secretion did not affect aphid fecundity, but secretion in the second instar enhanced life table parameters, whereas secretion in the fourth instar affected them negatively, suggesting a higher cost of secretion in later instars. Secretion in either instar improved host suitability for L. fabarum . Although control and treated aphids were parasitized at similar rates, and with similar success, wasps developed faster and emerged as larger adults in aphids that had secreted, regardless of instar. Transgenerational effects were also evident. Progeny emergence was higher when parental wasps developed in fourth instars than in seconds, whether aphids secreted or not, and progeny were larger when parental hosts secreted in the second instar, but not in the fourth. Secreting fourth instars were preferred to controls by L. fabarum females in choice tests, but not secreting second instars, and fourth-instar secretion improved wasp emergence. When control aphids were attacked, second instars were more likely to secrete than fourth instars, whereas the latter were more likely to kick the parasitoid. Cornicle secretion reduced the probability of subsequent secretion events and the frequency of other aphid defensive behaviors, indicating energetic tradeoffs among defensive tactics. Overall, our results revealed that cornicle secretion by immature A. fabae exacts both physiological and behavioral costs and results in improved host suitability for its parasitoid.